Self-Directed Learning for Nonnative English-Speaking Graduate Students Across Disciplines: Translanguaging Practices and Perspectives - Shi, Hong (Journal of International Students, 2021)
The influx of international students in U.S. colleges has resulted in linguistically diverse classrooms, raising attention to translanguaging practices. The purpose of this study is to examine the self-directed translanguaging practices and perspectives of nonnative English-speaking (NNES) graduate students in the U.S. university setting by using narrative stories, individual interviews, and focus group discussion. Twelve NNES graduate students from Asian countries participated in this research. These students demonstrated their self-management, motivation and persistence, and self-monitoring in their academic learning. Although they reported the difficulties from academic English language, they identified the value of translanguaging practices, and they developed some characteristics of autonomous learning due to “teacher-directed translanguaging” and “student-directed translanguaging.” Scaffolding and collaborative learning benefited and effectively engaged NNES graduate students in self-directed learning.